1999
DOI: 10.1097/00001756-199907130-00019
|View full text |Cite
|
Sign up to set email alerts
|

A ventrorostral belt is adjacent to the guinea pig primary auditory cortex

Abstract: The previously defined anterior area (A) of guinea pig auditory cortex has been divided into a large dorsal portion identified as the primary area (AI) and a smaller ventrorostral belt (VRB). This division is based on: (1) the much longer response latency of units in VRB (21.7 ms) than AI (14.1 ms); (2) the absence of pure onset units in VRB (i.e. units that lacked a sustained response), which are common in AI; (3) the weakness of noise-induced evoked potentials in VRB compared to AI; (4) units in VRB had lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…STRFs recorded in VRB also displayed response properties that were consistent with those previously reported for this area, i.e. long-latency, sustained excitation [Wallace et al, 1999] and overall, the area showed a significant difference in the distribution of STRF types compared to A1 and DC. Thus, VRB may be biased towards extracting different spectrotemporal features compared to A1 and DC, i.e.…”
Section: Comparison Of Strfs Between A1 and Other Fieldssupporting
confidence: 87%
See 3 more Smart Citations
“…STRFs recorded in VRB also displayed response properties that were consistent with those previously reported for this area, i.e. long-latency, sustained excitation [Wallace et al, 1999] and overall, the area showed a significant difference in the distribution of STRF types compared to A1 and DC. Thus, VRB may be biased towards extracting different spectrotemporal features compared to A1 and DC, i.e.…”
Section: Comparison Of Strfs Between A1 and Other Fieldssupporting
confidence: 87%
“…In addition, the basic response properties of a unit such as the preference for noise or pure-tone bursts and the latency were also used to identify its location. As described in previous studies, units in field A1 and DC were characterised by relatively short-latency, onset type responses (mean latencies = 14.4 and 14.6 ms in A1 and DC, respectively), whilst units in the ventrorostral belt (VRB) showed longer-latency (24.0 ms), sustained responses [Wallace et al, 1999[Wallace et al, , 2000. In the dorsorostral Fig.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…We are currently investigating the mechanisms of such corticofugal modulation. Following earlier work at lower levels of the system, in acute experiments we are characterising the different regions of the guinea pig auditory cortex (Rutkowski et al, 2002;Rutkowski et al, 2000;Wallace et al, 1999Wallace et al, , 2000aWallace et al, , 2002aWallace et al, , 2005aWallace et al, 2000b;Wallace et al, 2005b;Wallace et al, 2002b). However, we have recently begun to bridge the gap between our earlier work in lower levels of the auditory pathway (up to and including the inferior colliculus) and the cortical work with a series of studies of the auditory thalamus.…”
Section: Corticofugal Modulation Of Auditory Processingmentioning
confidence: 99%